Freeze-all cycles for normal responders: Is this way forward? - Satish Sharma; Shalaka Mhatre; Ashwini Jadhav; Nikita Lad (MGM Journal of Medical Sciences)
Background: The freeze-all approach has gained traction in in vitro fertilization (IVF) practices, and this study explores its benefits for normal responders. Aims and Objectives: The study evaluates whether the freeze-all strategy is advantageous in normal responders, irrespective of ovarian response. Materials and Methods: A retrospective study was conducted at a private IVF center, analyzing 225 oocyte retrieval cases and 170 frozen embryo transfers performed between January 2023 and February 2024. All patients underwent controlled ovarian stimulation using a gonadotropin-releasing hormone antagonist regimen, with the freeze-all policy applied. Fresh embryo transfers were postponed, and all embryos were cryopreserved. Frozen–thawed embryo transfers (FET) were performed in subsequent cycles. Results: The implantation rate for cleavage-stage FETs was 13.79%, whereas for blastocyst-stage transfers, it was 31.61%. The clinical pregnancy rate was 43.75% for cleavage-stage and 47.40% for blastocyst-stage FETs. Conclusion: The freeze-all approach can enhance IVF outcomes. However, an individualized treatment plan is essential for optimizing results, as there are currently no noninvasive clinical methods to determine, which patients would benefit most from a freeze-all strategy.